A Review of Recent Research Results on Soot: The Formation of a Kind of Carbon-Based Material in Flames - Xi, Jianfei; Yang, Guoqing; Cai, Jie; Gu, Zhongzhu (Frontiers in Materials, 2021)
As a product generated from incomplete combustion, soot is harmful to people's health and the environment. In recent decades, much attention has been paid to the control of soot generation in combustion systems. Efforts to reduce soot emissions depend on a basic understanding of the physical and chemical pathways from fuel to soot particles in flames. At the same time, flame synthesis method has become an alternative method for the preparation of carbon nanomaterials because of its advantages of low cost and mass production. Carbon-based materials can be synthesized within the sooting zones in flames. The research of soot formation mechanism in flames can provide support for the synthesis of carbon nanomaterials. In this paper, the effects of additives, temperature, and fuel type on soot formation characteristics and soot nanostructure in diffusion flames are reviewed. The deficiencies and prospects are put forward for future research.